Performance Evaluation of RF Terminators in Butler Matrix System at 28 GHz - Md Jizat, Noorlindawaty; Afiqah, Ayuni; Zainuddin, Norsiha; Abdullah, Norazah; Yamada, Yoshihide (International Journal of Integrated Engineering, 2025)
In wireless network systems, Radio Frequency (RF) terminators play a crucial part in preventing signal reflections and minimizing losses. In general, systems designed with 50 Ω or 75 Ω terminators experience lower signal losses and improved stability. As wireless technology advances, high-frequency systems and beamforming have become important. However, these systems are often susceptible to external interference from nearby devices, leading to unwanted signals that interrupt measurement precision and contribute to additional signal losses. Such interference is inevitable due to the sensitivity of the signals. To mitigate the effect, researchers have used metamaterial absorbers, beamforming enhancement, interference cancellation, and cognitive radio techniques. Despite advance technique presented, metamaterials suffer with resonance induced reflection. Additionally, problems arise when managing multiple signal path, matching technique and signal distortion often appear. Terminator passively absorb reflection signal, minimize crosstalk and ensuring stable system, which makes it the best choice to overcome the problem. This paper studies the effect of RF terminators on the performance of a beamforming Butler Matrix, focusing on key elements of current distribution, S-parameters, and output phase. The simulation and measurement results show stable and consistent outputs, with no ripple or distortion when the terminator is applied. The measurement of branch-line coupler indicates a return loss, S₁₁ of -17.9 dB, implying minimal signal reflection while the insertion loss, S₂₁ and coupling, S₃₁ of -3 ± 1 dB, indicates that half of the power is transmitted and equally coupled to the output and the isolation. In addition, S₄₁ is -18 dB, confirming good isolation between output ports. The measured return loss of the Butler Matrix is below -10 dB, showing minimal signal reflection, while the transmission amplitude is 6 ± 3.1 dB, reflecting stable signal transmission with small variation. Isolation between ports ranges from -14 dB to -32.2 dB, providing excellent isolation. The output phase has an average deviation of ±10°, ensuring consistent phase performance, highlighting the importance of RF terminators for future research in wireless communication.